2008
DOI: 10.1002/ijc.23601
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of colon cancer after external radiation therapy for prostate cancer

Abstract: Radiotherapy can induce second cancers. Controversies still exist regarding the risk of second malignancies after irradiation for prostate cancer. We evaluated the risk of developing colon and rectum cancers after prostate cancer in irradiated and nonirradiated patients. Using data from the population-based Geneva cancer registry, we included in the study all men with prostate cancer diagnosed between 1980 and 1998 who survived at least 5 years after diagnosis. Of the 1,134 patients, 264 were treated with exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 19 publications
1
31
0
2
Order By: Relevance
“…Since the rectum and bladder are definitively considered irradiated fields during RT for prostate cancer, it is reasonable that these tissues will receive more radiation dosage than other parts of the human body. However, in the subgroup analysis, no significantly increased secondary malignancy risk was observed; this is consistent with most studies [13,14,17,18,19,20]. Similarly, relevant parts of the bladder also receive radiation doses.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Since the rectum and bladder are definitively considered irradiated fields during RT for prostate cancer, it is reasonable that these tissues will receive more radiation dosage than other parts of the human body. However, in the subgroup analysis, no significantly increased secondary malignancy risk was observed; this is consistent with most studies [13,14,17,18,19,20]. Similarly, relevant parts of the bladder also receive radiation doses.…”
Section: Discussionsupporting
confidence: 78%
“…Two studies analyzed the hazards ratio (HR) of patients receiving RT over radical prostatectomy, one only reported HR without 95% CIs, and another included cancers occurring within the first 6 months after the start of the treatment, which were excluded [15,16]. Other four studies investigating the standardized incidence ratio (SIR), which was defined as the ratio between the observed and expected number of cases with the general population as the reference, were included for qualitative synthesis (table 1) [17,18,19,20]. …”
Section: Resultsmentioning
confidence: 99%
“…They compared men diagnosed with PCa between 1974 and 1994 with the general population and found an SIR of 0.8 (95%CI: 0.6–0.8) [18]. A more recent Swiss study based on the Geneva Cancer Registry showed that the overall SIR of secondary cancer in PCa patients treated with radiotherapy was 1.35 (p = 0.056), with elevated SIRs especially for colon cancer (4.0 (95%CI: 1.8–7.6)) [19].Our results confirm these more recent findings; however the SIR for colon cancer was only 1.40 and not statistically significant. The latter may be partly due to a smaller sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect to be regarded is the induction of a second cancer by radiotherapy [26]. The risk of getting a colon cancer after radiotherapy of the prostate might be reduced by decreasing the number of monitor units.…”
Section: Discussionmentioning
confidence: 99%